In logic, converse nonimplication[1] is a logical connective which is the negation of converse implication (equivalently, the negation of the converse of implication).
Converse nonimplication is notated
P\nleftarrowQ
P\not\subsetQ
\neg(P\leftarrowQ)
\negP\wedgeQ
The truth table of
A\nleftarrowB
Converse nonimplication is notated , which is the left arrow from converse implication (), negated with a stroke .
Alternatives include
\subset
falsehood-preserving: The interpretation under which all variables are assigned a truth value of 'false' produces a truth value of 'false' as a result of converse nonimplication
Example,
If it rains (P) then I get wet (Q), just because I am wet (Q) does not mean it is raining, in reality I went to a pool party with the co-ed staff, in my clothes (~P) and that is why I am facilitating this lecture in this state (Q).
Q does not imply P.
Converse Nonimplication in a general Boolean algebra is defined as .
Example of a 2-element Boolean algebra: the 2 elements with 0 as zero and 1 as unity element, operators as complement operator, as join operator and as meet operator, build the Boolean algebra of propositional logic.
and | and | then \scriptstyle{y\nleftarrowx}\ | means | ||||
---|---|---|---|---|---|---|---|
(Negation) | (Inclusive or) | (And) | (Converse nonimplication) |
Example of a 4-element Boolean algebra: the 4 divisors of 6 with 1 as zero and 6 as unity element, operators
\scriptstyle{c
\scriptstyle{\vee}
\scriptstyle{\wedge}
and | and | then \scriptstyle{y\nleftarrowx}\ | means | ||||
---|---|---|---|---|---|---|---|
(Co-divisor 6) | (Least common multiple) | (Greatest common divisor) | (x's greatest divisor coprime with y) |
r\nleftarrow(q\nleftarrowp)=(r\nleftarrowq)\nleftarrowp
rp=0
r=0
p=0
Clearly, it is associative if and only if
rp=0
q\nleftarrowp=p\nleftarrowq
q=p
0\nleftarrowp=p
{p\nleftarrow0=0}
1\nleftarrowp=0
p\nleftarrow1=p'
p\nleftarrowp=0
q → p
q\nleftarrowp
Converse Nonimplication is noncommutative | |||||
---|---|---|---|---|---|
Step | Make use of | Resulting in | |||
s.1 | Definition | \scriptstyle{q\tilde{\leftarrow}p=q'p}\ | |||
s.2 | Definition | \scriptstyle{p\tilde{\leftarrow}q=p'q}\ | |||
s.3 | s.1 s.2 | \scriptstyle{q\tilde{\leftarrow}p=p\tilde{\leftarrow}q \Leftrightarrow q'p=qp'}\ | |||
s.4 | \scriptstyle{q} | \scriptstyle{=} | \scriptstyle{q.1} | ||
s.5 | s.4.right - expand Unit element | \scriptstyle{=} | \scriptstyle{q.(p+p')} | ||
s.6 | s.5.right - evaluate expression | \scriptstyle{=} | \scriptstyle{qp+qp'} | ||
s.7 | s.4.left = s.6.right | \scriptstyle{q=qp+qp'}\ | |||
s.8 | \scriptstyle{q'p=qp'} | \scriptstyle{ ⇒ } | \scriptstyle{qp+qp'=qp+q'p} | ||
s.9 | s.8 - regroup common factors | \scriptstyle{ ⇒ } | \scriptstyle{q.(p+p')=(q+q').p} | ||
s.10 | s.9 - join of complements equals unity | \scriptstyle{ ⇒ } | \scriptstyle{q.1=1.p} | ||
s.11 | s.10.right - evaluate expression | \scriptstyle{ ⇒ } | \scriptstyle{q=p} | ||
s.12 | s.8 s.11 | \scriptstyle{q'p=qp' ⇒ q=p}\ | |||
s.13 | \scriptstyle{q=p ⇒ q'p=qp'}\ | ||||
s.14 | s.12 s.13 | \scriptstyle{q=p \Leftrightarrow q'p=qp'}\ | |||
s.15 | s.3 s.14 | \scriptstyle{q\tilde{\leftarrow}p=p\tilde{\leftarrow}q \Leftrightarrow q=p}\ | |||
Implication is the dual of Converse Nonimplication | |||||
---|---|---|---|---|---|
Step | Make use of | Resulting in | |||
s.1 | Definition | \scriptstyle{\operatorname{dual}(q\tilde{\leftarrow}p)} | \scriptstyle{=} | \scriptstyle{\operatorname{dual}(q'p)} | |
s.2 | s.1.right - .'s dual is + | \scriptstyle{=} | \scriptstyle{q'+p} | ||
s.3 | s.2.right - Involution complement | \scriptstyle{=} | \scriptstyle{(q'+p)''} | ||
s.4 | s.3.right - De Morgan's laws applied once | \scriptstyle{=} | \scriptstyle{(qp')'} | ||
s.5 | s.4.right - Commutative law | \scriptstyle{=} | \scriptstyle{(p'q)'} | ||
s.6 | s.5.right | \scriptstyle{=} | \scriptstyle{(p\tilde{\leftarrow}q)'} | ||
s.7 | s.6.right | \scriptstyle{=} | \scriptstyle{p\leftarrowq} | ||
s.8 | s.7.right | \scriptstyle{=} | \scriptstyle{q → p} | ||
s.9 | s.1.left = s.8.right | \scriptstyle{\operatorname{dual}(q\tilde{\leftarrow}p)=q → p}\ | |||
An example for converse nonimplication in computer science can be found when performing a right outer join on a set of tables from a database, if records not matching the join-condition from the "left" table are being excluded.[2]